نتائج بضع المحفظة الخلفية بالنيوديميوم ياغ ليزر - جلول قحطان (Latakia University Journal -Medical Sciences Series, 2013)
أجري البحث في مشفى الأسد الجامعي في اللاذقية في الفترة بين كانون الثاني من عام 2009 وكانون الثاني عام 2011 وشمل 80 عين ذات عدسة كاذبة لـ 80 مريض [36 عين (ذكور) (45%), 44 عين (اناث) (55%)] بعمر أكبر من 15 سنة, لديهم تكثف في المحفظة الخلفية مع انخفاض في القدرة البصرية بمقدار سطرين على لوحة سنلن. وقد تم تحديد القدرة البصرية قبل إجراء البضع بالياغ الليزر كما تم فحص جميع المرضى على المصباح الشقي من أجل قياس الضغط داخل المقلة ولنفي أي سبب آخر لتدني القدرة البصرية عدا تكثف المحفظة الخلفية. تم إجراء فتحة بقطر 2-3 ملم بالياغ ليزر وباستخدام عدسات ابراهام لبضع المحفظة الخلفية بعد تطبيق قطرة مخدر موضعي, وقد تم تطبيق أقل طاقة ممكنة وأقل عدد ممكن من الضربات. ثم تمت مراقبة المرضى لتحديد أفضل قدرة بصرية بعد البضع والاختلاطات المحتملة بعد استخدام الليزر مباشرة ومن ثم في نهاية الأسبوع الأول والثاني والرابع. - أعطيت المعالجة بعد استخدام الليزر اعتمادا على الاختلاطات التي حدثت عند كل مريض. * كانت أنماط تكثف المحفظة الخلفية كالتالي: - تليف في 54 عين (67.5%), لآلئ ايلشينغ في 16 عين (20%), تجعد أو انكماش في 10 عيون (12.5%). * كما كانت القدرة البصرية قبل تطبيق الياغ الليزر كالتالي: 6/60 في 42 عين (52.5%), 6/36-6/24 في 23 عين (28.75%), 6/18-6/12 في 15 عين (18.75%). *تحسنت القدرة البصرية بعد تطبيق الياغ الليزر إلى 6/9-6/6 في 60 عين (75 %). - حدثت الاختلاطات في 10 عيون (12.5%) بسبب الياغ ليزر وكانت كالتالي: - تنقر العدسة المزروعة داخل العين في 4 عين (5%), ارتفاع الضغط داخل العين في عين واحدة (1.25%), التهاب العنبة في 2عيون (2.5%) نزف قزحية (نزف بيت امامي) في عين واحدة (1.25%), زجاجي في البيت الأمامي في عين واحدة (1.25%), وذمة لطخة كيسية في عين واحدة (1.25%), لم تشاهد اختلاطات خطيرة مثل انفصال الشبكية أو ثقب اللطخة. - في 20 عين (25 %) لم يتحقق تحسن ملحوظ في القدرة البصرية بسبب وجود أمراضية في القسم الخلفي من العين لم يتم اكتشافها قبل البضع بسبب سماكة التكثف في المحفظة الخلفية. وبالتالي فإن بضع المحفظة الخلفية بالياغ ليزر إجراء فعال وطريقة مناسبة لإجراء البضع لجميع أنماط تكثف المحفظة الخلفية ولا يحدث فيه التهاب باطن العين الذي من الممكن أن يحدث بالبضع الجراحي. The research has been done in Alassad University Hospital in Lattakia, from January 2009 to January 2011 and included 80 pseudophakic eyes of 80 patients ] 36 (45.0%) belonged to male sex and 44 (55.0%) females[ older than 15 years having PCO with decreased best corrected Visual Acuity (VA) of two or more Snellen’s chart line. Before laser treatment, the VA was assessed and all patients were examined on slit lamp for IOP and to rule out the causes for reduced vision other than PCO. Then 2-3 mm size capsulotomy was done with Q-switched Nd: YAG Laser, with Abraham’s posterior capsulotomy lens, after topical anesthesia, by using minimum amount of energy and fewest numbers of pulses. Patients were followed for assessment of best corrected VA and for possible complications just after laser and at the end of 1st week, 2nd week and the 4th week. The post-laser treatment was advised in accordance with complications to each patient. The types of PCO were fibrosis in 54 (67.5%) eyes, Elschnig pearls in 16 (20 %) eyes and wrinkling in 10 (12.5%) eyes. Pre-laser visual acuity was CF-6/60 in 42 (52.5%) eyes, 6/36-6/24 in 23 (28.75%) eyes and 6/18-6/12 in 15 (18.75%) eyes. Post-laser VA was improved to 6/9-6/6 in 60 (75%) eyes. Out of 80 patients, 10 (12.5%) eyes developed the complications due to YAG laser which included IOL pitting in 4 (5%) eyes, raised IOP in 1 (1.25%), uveitis in 2 (2.5%), iris bleeding (hyphema) in 1 (1.25%), vitreous in anterior chamber in 1 (1.25%), and cystoids macular edema (CME) in 01(1.25%) eye. None of the eye developed sight threatening complications like retinal detachment or macular hole. The 20 (25%) eyes did not achieve the significant improvement because of pre-existing pathology in the posterior segment that was not diagnosed at the time of screening due to thick PCO. This means that Nd: YAG laser capsulotomy is effective and convenient method for doing capsulotomy in all types of PCO. It is free from the risk of endophthalmitis found in surgical capsulotomy.